A hybrid approach for estimating the drawbead restraining force in sheet metal forming - Duarte,E. N. (2010)
In order to achieve better part quality in sheet metal forming the rate of the material flow into the die cavity must be efficiently controlled. This control is obtained using a restraining force supplied either by the blankholder tool, drawbeads or both. When the restraining force required is too high, the use of drawbeads is necessary, although excessive blank deformation may be produced. Some other disadvantages such as adjustment difficulties during die try-outs to determine the actual Drawbead Restraining Force (DBRF) may also be encountered. One way to solve these problems and to reduce the number of die try-outs - which are very much time consuming - is to introduce/define accurate enough drawbead concepts. The present study will make use of a method that has been developed using the similitude approach in order to understand the influence of the most important parameters on DBRF and to establish a pre-estimate DBRF theory. Data bases have been developed throughout Explicit Dynamic Finite Element Method (EDFEM) based simulations. The results are compared with experimental data bases provided by Nine (1978) and with the analytical model of Stoughton (1988) results. The average of absolute error with respect to experimental data bases was around 6% and, for the studied cases, the maximum discrepancy was found to be below 11%. For the analytical and experimental cases, the average of absolute error was approximately 5% and, for the studied cases, the maximum error was below 7%. In terms of precision, the predictions derived from this approach are adequate when compared with analytical and experimental results. For this reason, the approach has been validated and accepted as a contribution to STAMPACK®, a commercial explicit dynamic finite element based system for forming processes numerical simulation.